Weather Modeling and Forecasting of PV Systems Operation - Paulescu, Marius; Paulescu, Eugenia; Gravila, Paul.; Badescu, Viorel; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
In the past decade, there has been a substantial increase of grid-feeding photovoltaic applications, thus raising the importance of solar electricity in the energy mix. This trend is expected to continue and may even increase. Apart from the high initial investment cost, the fluctuating nature of the solar resource raises particular insertion problems in electrical networks. Proper grid managing demands short- and long-time forecasting of solar power plant output. Weather modeling and forecasting of PV systems operation is focused on this issue. Models for predicting the state of the sky, nowcasting solar irradiance and forecasting solar irradiation are studied and exemplified. Statistical as well as artificial intelligence methods are described. The efficiency of photovoltaic converters is assessed for any weather conditions. Weather modeling and forecasting of PV systems operation is written for researchers, engineers, physicists and students interested in PV systems design and utilization.
The future of the energy mix paradigm -- Solar radiation measurements -- State of the sky assessment -- Stability of the radiative regime -- Modeling Solar Radiation at the Earth Surface -- Time series forecasting -- Fuzzy logic approaches -- Air temperature based models -- Outdoor operations of PV systems -- Forecasting the power output of PV systems -- Perspectives.
Keywords: Meteorology; Engineering mathematics; Renewable energy sources; Energy; Energy Harvesting; Renewable and Green Energy; Environmental Monitoring/Analysis.; Meteorology/Climatology.; Appl.Mathematics/Computational Methods of Engineering; Meteorology/Climatology.